2017
DOI: 10.1155/2017/1350375
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Preoperative versus Postoperative Dexamethasone on Postoperative Complications following Lower Third Molar Surgical Extraction

Abstract: Aim. To evaluate the effect of preoperative versus postoperative administration of oral Dexamethasone on postoperative complications including pain, edema, and trismus following lower third molar surgery. Methods. 24 patients were divided into two equal groups receiving 8 mg Dexamethasone orally, one group one hour preoperatively and the other group immediately after surgery. Pain was measured using VAS, edema was measured using a graduated tape between 4 fixed points in the face, and the mouth opening was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 17 publications
2
28
0
8
Order By: Relevance
“…These results are similar to those reported by Graziani et al, 24 Lima et al, 16 and Al-Shamiri et al, 25 which showed that pre-surgical oral administration of 8mg dexamethasone produced a significantly greater reduction in swelling compared to postoperative administration after the first hour, and on the first and third post-surgical days.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those reported by Graziani et al, 24 Lima et al, 16 and Al-Shamiri et al, 25 which showed that pre-surgical oral administration of 8mg dexamethasone produced a significantly greater reduction in swelling compared to postoperative administration after the first hour, and on the first and third post-surgical days.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of phospholipase A2 reduces arachidonic acid release, decreasing the levels of vasoactive substances: prostaglandins and leukotrienes. 4,6 These results differ with Al-Shamiri et al, 25 as their study showed that preoperative dexamethasone medication increased its analgesic effect, according to the VAS, and achieved significantly higher efficacy on the third day (2.6mm ± 1.5mm), compared to the group that received postoperative dexamethasone (3.2mm ± 1.5mm); p=0.008. Similarly, Boonsiriseth et al, 28 reported a similar analgesic effect on the first day after immediate post-surgical administration of intramuscular (20.8mm ± 21.3mm) and oral (22.4mm ± 24mm) dexamethasone, increasing progressively until the seventh postoperative day (2.2mm ± 5.5mm and 4.7mm ± 1.21mm; respectively); p>0.05.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…El tercer molar mandibular es el diente impactado más comúnmente encontrado en los seres humanos [1][2][3][4][5][6] y a menudo es tratado con una exodoncia quirúrgica, convirtiéndose así en una de las intervenciones más frecuentes en cirugía oral 1,[7][8][9][10][11][12][13][14] . Se sabe que cada cirugía conlleva riesgos y que la exodoncia quirúrgica de terceros molares se relaciona a menudo con secuelas posquirúrgicas importantes 1,[7][8][9][10][11][12][13]15,16 . Esta exodoncia varía en dificultad y en el grado de trauma causado a los tejidos circundantes.…”
Section: Introductionunclassified
“…Esta exodoncia varía en dificultad y en el grado de trauma causado a los tejidos circundantes. Por ello se requiere un conocimiento confiable de la profundidad y angulación de estas piezas dentales y su relación con las estructuras vitales circundantes, así como el manejo profesional de las complicaciones quirúrgicas asociadas 1,[7][8][9]11,13,15,17 .…”
Section: Introductionunclassified